Child-Report Measures of Occupational Performance: A Systematic Review. - Reinie Cordier; Yu-Wei Chen; Renée Speyer; Rebekah Totino; Kenji Doma; Anthony Leicht; Nicole Brown; Belinda Cuomo (PLoS ONE, 2016)
Introduction Improving occupational performance is a key service of occupational therapists and client-centred approach to care is central to clinical practice. As such it is important to comprehensively evaluate the quality of psychometric properties reported across measures of occupational performance; in order to guide assessment and treatment planning. Objective To systematically review the literature on the psychometric properties of child-report measures of occupational performance for children ages 2-18 years. Methods A systematic search of the following six electronic databases was conducted: CINAHL; PsycINFO; EMBASE; PubMed; the Health and Psychosocial Instruments (HAPI) database; and Google Scholar. The quality of the studies was evaluated against the COSMIN taxonomy of measurement properties and the overall quality of psychometric properties was evaluated using pre-set psychometric criteria. Results Fifteen articles and one manual were reviewed to assess the psychometric properties of the six measures-the PEGS, MMD, CAPE, PAC, COSA, and OSA- which met the inclusion criteria. Most of the measures had conducted good quality studies to evaluate the psychometric properties of measures (PEGS, CAPE, PAC, OSA); however, the quality of the studies for two of these measures was relatively weak (MMD, COSA). When integrating the quality of the psychometric properties of the measures with the quality of the studies, the PAC stood out as having superior psychometric qualities. Conclusions The overall quality of the psychometric properties of most measures was limited. There is a need for continuing research into the psychometric properties of child-report measures of occupational performance, and to revise and improve the psychometric properties of existing measures.